Violence against Women: Awareness, Knowledge and Attitudes of Male Civil Servants at the Ministries, Departments and Agencies in Owerri, Nigeria. (International Journal of Medical and Surgical Sciences, 2018)
Background: Violence against women (VAW) remains a huge and protracted public health concern. Also, there is growing recognition that the role men play in changing these inequalities in gender based power relations is critical. Documenting the trends of the aforestated role is essential to developing public health interventions to tackle VAW. Objective: To determine the awareness, knowledge and attitudes to VAW among male civil servants at the state and federal government ministries and agencies (MDAs) in Owerri, Nigeria. Materials and methods: This was a cross sectional survey of 326 male civil servants at the State and Federal Government MDAs in Owerri Nigeria, selected using multistage sampling technique from August 2016 to January 2017. Data were collected using pretested self-administered semi- structured questionnaires. Data were analysed using SPSS V.22. Statistical associations between variables were tested using Chi square, at p -value < 0.05. Results: The mean age of respondents was 40.6 ± 9.8. Three hundred and two (92.6%) of them were aware of VAW. Sources of information on VAW include: 184(57.9%) television, 171(53.8%) radio, 167(52.5%) print media, 152(47.8%) social media. The form of VAW mostly cited 227(70.7%) was rape, while the mostly practiced form of VAW 201(62.4%) was physical violence. Only 65 (20%) had good knowledge, while 151 (46.3%) had a good attitude towards VAW. There were statistically significant associations between respondent’s attitudes towards VAW and (religion [p =0.000], tribe [p =0.017]). Conclusions: This study revealed high awareness on VAW, poor knowledge about VAW and poor attitude towards the practice of VAW. We recommend sustained awareness and improved comprehensive gender equity cum attitudinal change education.